Progress-Based Strategy For User Engagement In mHealth Participatory Sensing - Syarulnaziah, Anawar; Saadiah, Yahya; Zakiah, Ayop; Andita Suci, Pratiwi (Asian Research Publishing Network (ARPN), 2016)
For a long time, outcome-based strategy is used as a basis of health standard in wellness program. However, in the case of mHealth participatory sensing the strategy is not always pertinent because the user of the platform is not limited to patient only, but also by a person who used the system for wellness maintenance, and by the stakeholders that collect and analyze information. To improve community’s engagement on health wellness and maintenance, we propose myCommHealth that emphasizes on progress-based strategy. myCommHealth is an open data collection platform using mobile devices and allow community and stakeholder to collect, analyze and submit or share health related The objective of this paper is two-fold: First, to explore the design principle behind progress-based strategy for user engagement in mHealth participatory sensing system. Second, to propose myCommHealth, a proof-of-concept prototype that incorporate intrinsic incentive, feedback, and self-monitoring tools to improve user participation in wellness and health-maintenance campaign.